Molecular epidemiology and whole genome sequencing analysis of clinical Mycobacterium bovis from Ghana. - Otchere ID; van Tonder AJ; Asante-Poku A; Sánchez-Busó L; Coscollá M; Osei-Wusu S; Asare P; Aboagye SY; Ekuban SA; Yahayah AI; Forson A; Baddoo A; et al. (PLOS, 2019)
Background Bovine tuberculosis (bTB) caused by Mycobacterium bovis is a re-emerging problem in both livestock and humans. The association of some M. bovis strains with hyper-virulence, MDR-TB and disseminated disease makes it imperative to understand the biology of the pathogen. Methods Mycobacterium bovis (15) among 1755 M. tuberculosis complex (MTBC) isolated between 2012 and 2014 were characterized and analyzed for associated patient demography and other risk factors. Five of the M. bovis isolates were whole-genome sequenced and comparatively analyzed against a global collection of published M. bovis genomes. Results Mycobacterium bovis was isolated from 3/560(0.5%) females and 12/1195(1.0%) males with pulmonary TB. The average age of M. bovis infected cases was 46.8 years (7-72years). TB patients from the Northern region of Ghana (1.9%;4/212) had a higher rate of infection with M. bovis (OR = 2.7,p = 0.0968) compared to those from the Greater Accra region (0.7%;11/1543). Among TB patients with available HIV status, the odds of isolating M. bovis from HIV patients (2/119) was 3.3 higher relative to non-HIV patients (4/774). Direct contact with livestock or their unpasteurized products was significantly associated with bTB (p<0.0001, OR = 124.4,95% CI = 30.1–508.3). Two (13.3%) of the M. bovis isolates were INH resistant due to the S315T mutation in katG whereas one (6.7%) was RIF resistant with Q432P and I1491S mutations in rpoB. M. bovis from Ghana resolved as mono-phyletic branch among mostly M. bovis from Africa irrespective of the host and were closest to the root of the global M. bovis phylogeny. M. bovis-specific amino acid mutations were detected among MTBC core genes such as mce1A, mmpL1, pks6, phoT, pstB, glgP and Rv2955c. Additional mutations P6T in chaA, G187E in mgtC, T35A in Rv1979c, S387A in narK1, L400F in fas and A563T in eccA1 were restricted to the 5 clinical M. bovis from Ghana. Conclusion Our data indicate potential zoonotic transmission of bTB in Ghana and hence calls for intensified public education on bTB, especially among risk groups..
Keywords: Adolescent; Adult; Aged; Animals; Cattle; Child; Comorbidity; DNA, Bacterial; Drug Resistance, Bacterial; Female; Ghana; HIV Infections; Humans; Male; Middle Aged; Molecular Epidemiology; Mutation; Mycobacterium bovis; Phylogeny; Tuberculosis, Bovine; Tuberculosis, Pulmonary; Whole Genome Sequencing; Young Adult